2001
DOI: 10.1212/wnl.56.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and incidence of multiple sclerosis in Catania, Sicily

Abstract: Article abstract-Objective: An epidemiologic survey was conducted to determine the prevalence and incidence of MS in the city of Catania, Sicily, Italy. Prevalence rate was calculated as point prevalence at January 1,1995, and incidence during 1974 to 1995. Methods: The authors studied the frequency of MS in the community of Catania in a population of 333,075 inhabitants according to the 1991 census. The primary sources for the case ascertainment were the neurologic and motor rehabilitation departments, the MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
0
2

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 21 publications
6
36
0
2
Order By: Relevance
“…■ Key words multiple sclerosis · prevalence · incidence · cluster lence day 1 January 1995) and a mean annual incidence for the period 1975-1994 of 2.3/100,000 [7]. These rates were close to those reported in continental Italy.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…■ Key words multiple sclerosis · prevalence · incidence · cluster lence day 1 January 1995) and a mean annual incidence for the period 1975-1994 of 2.3/100,000 [7]. These rates were close to those reported in continental Italy.…”
Section: Introductionsupporting
confidence: 69%
“…Several epidemiological surveys have been carried out also in Sicily where prevalence and incidence rates found during recent decades were close to those reported in continental Italy [3,7,[12][13][14].At the end of 90s we carried out an epidemiological survey in the city of Catania finding a prevalence rate of 58.5/100,000 (Preva-■ Abstract We carried out an epidemiological survey to determine prevalence and incidence of multiple sclerosis in the little town of Linguaglossa in the Province of Catania. We calculated prevalence rate as point prevalence at 1 January 2001 and incidence during 1991-2000.…”
Section: Introductionmentioning
confidence: 76%
“…More recently three studies have reported the prevalence rate in Sicily [4,10,11] with a very high figure in one specific area, as well as in Padua [12], with a prevalence of 80.5/100,000. The present study reports a higher prevalence rate in continental Italy.…”
Section: Discussionmentioning
confidence: 99%
“…The pain severity in MS can be severely debilitating (Ehde et al, 2006) and MS patients exhibit cold allodynia and mechanical hyperalgesia (Svendsen et al, 2003), symptoms typically found in non-MS patients suffering from chronic pain conditions. MS shows significant gender differences in incidence and disease progression with women having a 2:1 higher incidence of MS (Vein et al, 1995;Ford et al, 1998;McDonnell and Hawkins, 1998;Moreau et al, 2000;Totaro et al, 2000;Nicoletti et al, 2001), but with males developing more severe clinical symptoms and deteriorating faster (Wynn et al, 1990;Bronnum-Hansen et al, 1994;Vein et al, 1995;Cottrell et al, 1999). Gender differences are not only evident in MS prevalence, but also in MS pain.…”
Section: Introductionmentioning
confidence: 99%